Changes in pre‐haemodialysis serum creatinine levels over 2 years and long‐term survival in maintenance haemodialysis - Seok Hui Kang; Gui Ok Kim; Bo Yeon Kim; Eun Jung Son; Jun Young Do; Jung Eun Lee (Wiley, 2024)
Abstract Background Pre‐haemodialysis (HD) serum creatinine levels are reliable and inexpensive markers of muscle mass and important predictors of survival in patients with stable chronic HD. We aimed to assess whether changes in pre‐HD serum creatinine levels during a 2‐year period are linked to long‐term patient survival. Methods We retrospectively analysed patients enrolled in a periodic HD quality assessment program. Of the 21 846 participants in the fourth HD quality assessment program, 13 765 were presented in the fifth, of which 10 299 eligible patients were included in this study. We assessed the change in serum creatinine levels over 2 years. The patients were categorized into the following three groups: stable group (patients with change in serum creatinine < 1 mg/dL during 2 years of HD, n = 5664), increasing group (patients with increase in serum creatinine ≥ 1 mg/dL, n = 2419) and decreasing group (patients with decrease in serum creatinine ≥ 1 mg/dL, n = 2216). Results The duration of HD at baseline was 62-83 months, with diabetic kidney disease being the most common cause of kidney failure in 36.4% of patients. The 5‐year patient survival rates in the stable, increasing and decreasing groups were 69.1%, 71.3% and 66.8%, respectively. The decreasing group had poorer patient survival than the other two groups (P = 0.083 for stable vs. increasing group; P = 0.011 for stable vs. decreasing group; P < 0.001 for increasing vs. decreasing group). There was no significant difference in the cardiovascular event‐free survival rate among the three groups. Multivariable Cox regression analyses revealed the highest hazard ratio (HR) for mortality in the decreasing group (HR 1.33, 95% confidence interval [CI] 1.21-1.45, P < 0.001 vs. stable group; HR 1.50, 95% CI 1.34-1.69, P < 0.001 vs. increasing group). The increasing group exhibited a lower risk of mortality than the stable group (HR 0.88, 95% CI 0.81-0.97, P = 0.008). Subgroup analyses based on age, HD vintage, sex, Charlson comorbidity index score, presence of diabetes and baseline serum creatinine level tertiles revealed that the decreasing group exhibited the highest mortality among all subgroups. Conclusions Our results demonstrate that changes in pre‐HD serum creatinine levels over 2 years of HD were associated with all‐cause mortality in patients undergoing HD. This finding suggests a simple and promising approach for clinicians in the prognosis and management of patients undergoing HD.